Review Essay: Classical Studies as a Starting Point. A Comprehensive and Easy-to-Understand Introduction to Selected Qualitative Research Approaches - Johner-Kobi, Sylvie (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
In his book, Patrick HEISER introduces commonly utilized qualitative research approaches, data collection methods, and data analysis techniques using four classical studies. The author chose the study "Die Arbeitslosen von Marienthal" [The Sociography of an Unemployed Community] (JAHODA, LAZARSFELD & ZEISEL 1975 [1933]) to illustrate ethnography and participant observation; the study on unemployed teachers (ULICH, HAUSSER, MAYRING, STREHMEL & KANDLER 1985) to discuss the expert interview and qualitative content analysis; the study on community mergers and community power structures (SCHÜTZE 1976) for the narrative interview as well as narrative analysis; and "Awareness of Dying" (GLASER & STRAUSS 1965) to discuss grounded theory methodology. Each of the studies presented is evaluated with reference to two different quality criteria of qualitative research. Patrick HEISER's text is a clearly written introductory work that gives students of sociology and related fields a comprehensive insight into frequently used qualitative data collection methods and, in particular, data analysis techniques.